TURNING STONES: DESCRIPTIVE AND PRELIMINARY EVALUATION FINDINGS OF AN INDIGENOUS, FAMILY-CENTERED DOMESTIC VIOLENCE INTERVENTION PROGRAM (Canadian Journal of Native Studies, 2026)
AbstractTurning Stones is a family-centered domestic violence intervention programin British Columbia, Canada. This culturally sensitive programserves Indigenous men, women, and youth/children who suffer as a resultof abuse in one or more intimate relationships. The study describesthe Turning Stones program and provides a preliminary examinationof program impacts based on nine men and nine women enrolled inthe program. The program shows promising results with respect todecreasing abusive behaviours, with participants reporting declinesin both physical and psychological abuse following program completion.Male participants also demonstrated gains in knowledge and skillsconcerning anger reduction. The limitations of the study and future researchare discussed.